India's Kochi Biennale: sponsorship, patronage, and art's resistance. (7th May 2019) - Joy, Annamma; Belk, Russell
Abstract : Purpose: The purpose of this paper is to examine the meaning, in both local and international context, of the Kochi-Muziris Biennale (KMB), the first international exhibit of contemporary art in India. Kochi Biennale Foundation (KBF), which administers the KMB, identifies art as a means for transforming society, with a mission to bring global contemporary art to India and to present India's modern art to the world. The authors further investigate the role of government sponsorship and corporate patronage in funding the KMB, and investigate how resistance through art is key to the KMB's identity. Design/methodology/approach: This study focuses primarily on published materials relating to the KMB. One of the authors attended the 2016 KMB and interviewed fellow attendees. Additionally, the authors reviewed and assessed social media postings regarding the 2016 KMB. Findings: The authors argue that government sponsorship and corporate patronage are never solely about political or financial power. Rather, a generalized reciprocity among the three entities – corporations, the government and the artists – allows the KMB to flourish. For the artists involved, the KMB, co-founded by activist artists, sustains interest in and awareness of resistance. Originality/value: Extant literature on biennales is sparse on ways in which these exhibits extend their impact beyond the art world. The authors examine issues such as India expanding its position on the world stage through art, and the implications of political resistance embraced by Indian artists on future directions for the KMB, that have heretofore been unaddressed.